Pengaruh Akuntansi Keperilakuan Terhadap Penyusunan Laporan Keuangan dan Sistem Informasi Akuntansi - Septa Dinda Alfia, Famia; Trisnaningsih, Sri (GEMA EKONOMI, 2023)
Accounting has several fields of knowledge, namely behavioral accounting which explains the relationship between behavior and the accounting system, behavioral accounting is an organization and accounting system whose existence is acknowledged. As for behavioral accounting is a study of the behavior of accountants and non-accountants who are influenced by functions and reporting. Accounting is an information system that identifies a record and communicates economic incidents in an organization to interested users. The so-called users in this case are external parties of the company such as investors, creditors and government agents, while the internal parties of the company are the managers and employees of the company. Accounting plays an important role as a company's financial controller that can be used to evaluate and make plans for the company's future. The purpose of this study is to find out how behavioral accounting affects financial reports and accounting information systems. The research method used is to obtain data regarding articles that contain how behavioral accounting influences the preparation of financial reports from scholar, emerald, scimago journal and related web journal data. The results of the research conclude that the results of this literature review reveal that behavioral accounting has a positive effect on the preparation of financial reports and behavioral accounting has a positive effect on accounting information systems.